Assessment of knowledge of mothers on stunting: a survey in Perak Tengah - Hamlun, Nuraini; Khattak, Muhammad Muzaffar Ali Khan (2021)
Stunting has negative consequences not only for the child's physical growth, but also for his or her cognitive performances. Stunting can be caused by a various cause, including inappropriate child feeding due to a lack of awareness about feeding babies and toddlers which can be avoided by mothers who are the primary caregivers for their children. This study aimed to assess the level of knowledge among mothers regarding feeding infants and young children in relation to stunting problem. This was a cross-sectional study involving 106 mothers aged more than 18 years who lived in Perak Tengah district. The state of knowledge regarding infant and child feeding was evaluated using the knowledge section of the Food and Agriculture Organization (FAO) nutrition-related Knowledge, Attitude and Practice (KAP) questionnaire. Their total score was summed up and categorized into poor, moderate and high level of knowledge. Majority of the respondents scored higher level of knowledge which was 95.3% (n=101) while the other 4.7% (n=5) scored moderate level of knowledge. The findings demonstrated that there was a significant difference (p<0.05) in terms of knowledge level between secondary school and higher education among the mothers. Stunting knowledge among mothers 75.5% (n=80) were having a higher level of knowledge while the other, 24.5% of the mothers (n=26) were having a moderate level of knowledge. In conclusion, despite the higher prevalence of mothers who scored higher level of knowledge, it is still important for a mother to learn about this as the knowledge regarding feeding infants and children is very important to be acknowledged among mothers in prevention of nutritional problems in our country.